Design and simulation of continuous tuning band stop filter by2-D periodic defected ground structure. (November 2022) - Vali, Sk Shoukat; Rao, K. Srinivasa
Abstract: In this paper, the design and simulation of a continuous tuning bandstopfilter (BSF) is done by using two-dimensional (2-D) periodic DGS for the coplanar waveguide (CPW) transmission line. The proposed BSF filter structure has DGS cells on the ground plane of the CPW transmission line. This structure can easily be designed for another frequency band by changing the number of periodic DGS unit cells. This BSF has a fixed bandwidth of 8.2 GHz over a wide range of frequencies (16–26) GHz.The tunability of the BSF is achieved by moving plates, which are kept above the substrate of the CPW. The size of these plates is the same as the size of the DGS cell. The tunability of the BSF is observed while changing the distance between the metal plates and substrate in the up position. In the down position the metal plates are covered by the DGS cells, then the filter act as a normal transmission line. The extraction of the equivalent circuit model parameters has also been derived. The electromagnetic (EM) and equivalent model simulations are done with the HFSS and ADS tools, both these simulations have a good agreement with each other. From this, the proposed BSF can be used for satellite and radar communication in K band frequency range.